Analisis Exploratorio En La Industria De Quesos Artesanales En Escárcega, Campeche De Acuerdo A Los Prerrequisitos De Haccp - Maximiliano Vanoye Eligio; Jorge Isidro Xool Alfaro; José Ángel de Espinoza López; Jorge Emmanuel Arteaga Castillo (European Scientific Journal, ESJ, 2017)
This article presents a diagnosis of hygiene management based on the fulfillment of the prerequisites of a HACCP system, in three companies of the agrifood sector that operate in the municipality of Escárcega, Campeche, especially in the elaboration of artisanal cheeses. The evaluation methodology corresponded to the verification of compliance with the checklist of the instrument GHYCAL (Hygiene and Quality Management). The results allowed to find levels of hygiene management in a percentage scale and to classify the three companies in low level of compliance for all, due mainly to the little knowledge and technological development that is presented in the region.